Outcomes of Occupational Self-Efficacy in Older Workers. (April 2015) - Paggi, Michelle E.; Jopp, Daniela S.
Because of the increasing number of older workers, it is important to develop models of work-related constructs for this population. The present article developed a model surrounding occupational self-efficacy, testing its relation to other factors (e.g., intrinsic job motivation), predictors (e.g., self-perceptions of aging), and outcomes (e.g., job satisfaction). Employed adults of ages 50 and older ( n  = 313) were recruited via organizations and social media sites. Study participants ( M  = 59.7, SD  = 6.1, range = 50–78) volunteered to fill out an Internet survey. Occupational self-efficacy predicted job satisfaction, and intrinsic job motivation fully mediated this relationship. More negative self-perceptions of aging predicted poorer occupational self-efficacy. Occupational self-efficacy also predicted life satisfaction. Expected retirement age and job performance were unrelated to occupational self-efficacy. These findings may inform workplace interventions that seek to maintain or increase older worker job and life satisfaction.